2014
DOI: 10.1159/000356742
|View full text |Cite
|
Sign up to set email alerts
|

Homoharringtonine Combined with Cytarabine to Treat Chronic Myelogenous Leukemia in Myeloid Blast Crisis and Its Impact on Bone Marrow CD34+CD7+ Cells

Abstract: Background: The therapeutic response of chronic myelogenous leukemia in myeloid blast crisis (CML-MBC) is very poor. Aim: To explore the therapeutic effect of homoharringtonine (HHT) combined with cytarabine (HA regimen) on CML-MBC and its influence on bone marrow CD34+CD7+ cells. Results: Thirty-four patients with CML-MBC were treated with the HA regimen and bone marrow CD34+CD7+ cells were assayed prior to and after treatment. Among 33 evaluable patients, the overall hematological response (complete/partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…296 The study concluded that it is an effective treatment and that CD34 þ CD7 þ cells may be one of the valuable clinical parameters to assess treatment effectiveness.…”
Section: Other Clinical Applicationsmentioning
confidence: 99%
“…296 The study concluded that it is an effective treatment and that CD34 þ CD7 þ cells may be one of the valuable clinical parameters to assess treatment effectiveness.…”
Section: Other Clinical Applicationsmentioning
confidence: 99%
“…HHT (Synribo) is thought to act as a broad-spectrum protein tyrosine kinase inhibitor and was approved in 2012 by the FDA for the treatment of adult patients with CML or accelerated phase CML [ 49 ]. The therapeutic response of patients with CML in myeloid blast crisis (CML-MBC) is generally very poor, but a combination of HHT and cytarabine has been reported to be an effective treatment for CML-MBC [ 50 ].…”
Section: Cancer Chemotherapeutic Agents Derived From Terrestrial Planmentioning
confidence: 99%
“…In a small study of 34 patients treated with HA regimen, the overall HR rate was 60% and 21% had a cytogenetic response. 54 …”
Section: Homoharringtonine-based Regimensmentioning
confidence: 99%
“…In a small study of 34 patients treated with HA regimen, the overall HR rate was 60% and 21% had a cytogenetic response. 54 HHT-based therapies appear promising and merit further investigation in combination with third-generation TKIs.…”
Section: Homoharringtonine-based Regimensmentioning
confidence: 99%